Cyclin G2 Inhibits Oral Squamous Cell Carcinoma Growth and Metastasis by Binding to IGFBP3 and Regulating the FAK-SRC-STAT Signaling Pathway - Wang, Danning; Gao, Jinlan; Zhao, Chenyang; Li, Sen; Zhang, Di; Hou, Xiaoyu; Zhuang, Xinbin; Liu, Qi; Luo, Yang (Frontiers in Oncology, 2020)
The cell cycle protein cyclin G2 is considered a tumor suppressor. However, its regulatory effects and potential mechanisms in oral cancers are not well understood. This study aimed to investigate the effect of cyclin G2 on oral squamous cell carcinoma (OSCC). The data from 80 patients with OSCC were utilized to predict the abnormal expression of cyclin G2. The proliferation and metastasis were determined by a cell counting Kit-8 assay, flow cytometry, a wound-healing assay and a cell invasion assay. The expression of key proteins and genes associated with the cyclin G2 signaling pathways was determined by western blotting and real-time PCR, respectively. The orthotopic nude mice model was established by a mouth injection of SCC9 cells overexpressing cyclin G2. We showed that the low level of cyclin G2 in OSCC, which is negatively correlated with clinical staging, was a negative prognostic factor for the disease. We also found that cyclin G2 inhibited the proliferation, metastasis and blocked the cell cycle at G1/S of OSCC cells, suggesting that cyclin G2 has an inhibitory effect in OSCC. Mechanistically, cyclin G2 inhibited the growth and metastasis of OSCC by binding to insulin-like growth factor binding protein 3 (IGFBP3) and regulating the focal adhesion kinase (FAK) -SRC-STAT signal transduction pathway. Cyclin G2 competed with integrin to bind to IGFBP3; the binding between integrin and IGFBP3 was reduced after cyclin G2 overexpression, thereby inhibiting the phosphorylation of FAK and SRC. These results showed that cyclin G2 inhibited the progression of OSCC by interacting with IGFBP3 and that it may be a new target for OSCC treatment.